Rate of change in acetylcholine receptor antibody levels predicts myasthenia gravis outcome. Issue 9 (25th March 2021) - Kojima, Yuta; Uzawa, Akiyuki; Ozawa, Yukiko; Yasuda, Manato; Onishi, Yosuke; Akamine, Hiroyuki; Kawaguchi, Naoki; Himuro, Keiichi; Noto, Yu-ichi; Mizuno, Toshiki; Kuwabara, Satoshi
Abstract : Objective: To investigate the association between changes in anti-acetylcholine receptor antibody (AChR Ab) levels induced by immunosuppressive treatment and myasthenia gravis (MG) prognosis at 1-year post-treatment in patients with MG. Methods: We included 53 consecutive AChR Ab-positive patients with MG whose AChR Ab levels were remeasured within 100 days of initiating immunosuppressive treatment (median remeasuring time post-treatment: 71 (55–84) days). The AChR Ab level reduction rate (RR-AChRAb, %/day) adjusted for the time between treatment initiation, and AChR Ab level remeasurement was calculated as follows: (pretreatment–post-treatment AChR Ab level)/pretreatment AChR Ab level/days between therapy initiation and AChR Ab level remeasurement ×100. Participants were divided into two groups based on the cut-off value of RR-AChR Ab, determined using receiver operating characteristic analyses for achieving minimal manifestation (MM) or better status at 1-year postimmunosuppressive treatment. The Myasthenia Gravis Foundation of America postintervention status and MG activity of daily living (MG-ADL) score at 1-year post-treatment were compared between the two groups. Results: The RR-AChRAb cut-off value was 0.64%/day. The high RR-AChRAb group had a higher ratio of MM or better status (90% vs 65%, p=0.03) and lower MG-ADL score (median; 1 vs 2, p=0.04) than the low RR-AChRAb group. Kaplan-Meier analyses showed the early MM achievement in the high RR-AChRAb group (p=0.002, log-rank test). Conclusions: High RR-AChRAb is associated with a favourable outcome at 1-year post-treatment. AChR Ab remeasurement within 100 days of therapy may be useful for predicting AChR Ab-positive MG outcomes at 1-year post-treatment.